Tingkat Kesiapan Masyarakat Kota Semarang Terhadap Minat Teknologi Era Metaverse - Tjan, Gavina Jechonia Santoso; Devi Purnamasari (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
Metaverse is a virtual world concept where people can create and explore together with other internet users in the form of avatars. The capital city of Central Java, namely, Semarang City is still in the development stage to build a twin city of the Metaverse world, named Semarang City Metaverse City. Mayor of Semarang Hendrar Prihadi has revealed the development of Semarang Metaverse City. The purpose of this study is to determine the level of readiness of the people of Semarang city for interest in using Metaverse technology, especially in generation Y and generation Z. The independent variable used is the level of readiness and the technology readiness index and the dependent variable is interest in using technology. The population in this study were the people of the city of Semarang who were born in 1991 to 2005. The sample in this study used a cluster sampling technique with  total of 400 respondents. The method used in this study is quantitative with multiple linear regression analysis techniques. The results of this study indicate that the level of readiness and the technology readiness index have a significant effect on interest in using Metaverse technology.